2020
DOI: 10.5430/ijfr.v11n3p18
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Managerial Overconfidence, Audit Committee, CEO Duality and Audit Quality and Accounting Misstatements

Abstract: This paper discusses the relationships between managerial overconfidence, financial distress, audit committee, CEO duality and audit quality and the occurrence of material accounting misstatements by Malaysian listed companies. Managerial overconfidence and financial distress are viewed as motives for accounting misstatements in this study. Audit committee characteristics, i.e., independence and expertise of its members, CEO duality and audit quality are viewed as the ‘loopholes’ in corporate governance mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…In research from Palestine (2009) and Sanjaya (2008) which found that the audit committee is not able to influence earnings management. Research by Azhari et al (2020) found that the audit committee's expertise and independence were not significant in deterring accounting misstatements. Research from Haniffa et al (2006) and (Peasnell et al, 2005) also found no relationship between audit committee and earnings management.…”
Section: Effectivenessmentioning
confidence: 98%
“…In research from Palestine (2009) and Sanjaya (2008) which found that the audit committee is not able to influence earnings management. Research by Azhari et al (2020) found that the audit committee's expertise and independence were not significant in deterring accounting misstatements. Research from Haniffa et al (2006) and (Peasnell et al, 2005) also found no relationship between audit committee and earnings management.…”
Section: Effectivenessmentioning
confidence: 98%
“…The issue of accounting deception has been extensively studied in industrialized nations, whereas emerging economies have received far less attention (Lau & Ooi, 2016). Pakistan and other developing Asian nations have been the subject of very little research on accounting misrepresentation (Azhari, Hasnan, & Sanusi, 2020;Latif & Abdullah, 2015). Due to variations in legal frameworks, corporate structures, cultural norms, regulatory environments, and the caliber of financial reporting, outcomes may differ between nations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BoDs that have an overconfidence attitude tend to make inaccurate estimates or estimates. This action creates misreporting of accounting records (Azhari et al, 2020). BoD overconfidence increases the potential for overstatement, and it is not consistent with the conservatism principle (Ramsheh & Molanzari, 2014).…”
Section: Bod Overconfidence and Financial Restatementmentioning
confidence: 99%
“…Second, not many scholars have discussed the consequence of BoD overconfidence on the financial restatement. Most of the previous findings discuss the impact of managerial overconfidence on accounting conservatism (Hsu et al, 2017), accounting misstatement (Azhari et al, 2020), earning management (Berry-Stölzle et al, 2018;Sutrisno, 2019), and financial statements comparability (Almaleki et al, 2021). However, board overconfidence has two opposite consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation